Monitoring changes in sandy beaches in temperate areas through sandhoppers' adaptations - Scapini, Felicita; Fanini, Lucia; Gambineri, Simone; Nourisson, Delphine; Rossano, Claudia (Crustaceana, 2013)
Sandhoppers (Amphipoda, Talitridae) are keystone species of sandy beach ecosystems in temperate areas. Several traits have been studied and proposed as bioindicators of impacts on sandy beaches, at individual (physiology and behaviour), population (life cycle, abundance, population dynamics and structure, morphometry and fluctuating asymmetry) and species (genetic structure and variation) levels. Sandy beaches, where these species spend their whole life cycle, are dynamic environments, subject to periodic changes (night-day, tides and seasons), as well as to impacts that may cause erosion or accretion of the littoral zone. The first response of an animal to potentially injuring factors is shown by its avoidance behaviour regarding the potential stress. This behaviour may be a rapid escape reaction, shown by single individuals, the whole or part of the population. Activity rhythms, changes in zonation, burrowing, escape reactions, orientation towards the optimal zone on the beach, are all adaptations to environmental changes, increasing the survival chances of the individuals and populations that express such behaviours. In this paper we present case studies of the talitrid species' behavioural adaptations related to natural and human impacts on sandy beaches in the Mediterranean: (1) erosion/accretion dynamics of a Tyrrhenian beach in central Italy (Maremma Regional Park), and (2) increasing urbanisation on a beach in north-western Morocco (Oued Laou river mouth). The best behavioural adaptation was shown by the populations from more stable coastlines. For the survival value of rapid and possibly anticipatory responses to stressful factors, behavioural variation may be proposed as an early-warning indicator of environmental changes. The adaptation at higher levels (population and species) may reflect, on the one hand, the evolvability of the species and, on the other hand, the changeability of the environment. Adaptations at population level may be used as bioindicators of past changes over generations and evolutionary times.